Role of CT enterography in evaluation of small bowel disorders - Misra, Ritu N.; Bajaj, Sunil Kr. (International Journal of Research in Medical Sciences, 2019)
Background: Small bowel pathologies are an enigma for clinicians and difficult to assess and evaluate for clinicians. In order to establish the efficacy of MDCT Enterography in diagnostic characterisation of small bowel lesions, the current study was undertaken. Methods: A prospective observational cross-sectional study was carried out in a tertiary care hospital. 30 patients with clinically suspected small bowel disease underwent CT enterography using iso-osmotic mannitol as neutral enteral contrast. CT enterography diagnoses were compared with clinical, surgical and histopathological results. Results: CT enterography showed a sensitivity (95.83%), specificity (100%), positive predictive value (100%), negative predictive value (85.71%), accuracy (96.66%) in diagnosis of small bowel diseases. Conclusions: CTE is a non-invasive well tolerated and reliable imaging modality for the depiction of small-bowel diseases. It provides excellent visualization of luminal, mural and extraintestinal findings.